Layanan Penguasaan Konten untuk Meningkatkan Keterampilan Berbicara di Depan Umum Bagi Siswa - Gutara, Mohamad Yudha; Rangka, Itsar Bolo; Prasetyaningtyas, Wahyu Eka (JURNAL FOKUS KONSELING, 2017)
Abstract: Each student is essence able to speak but is constrained when they are to speak in public such as presentations and speakers. One of guidance and counseling services are effective to improve the ability to speak in public is a Content Mastery service. This research to find out about the Effectivity of Content Mastery Service to Improve Public Speaking Skills in Students SMKN 1 Gunungputri. This research using quantitative research method with experimental research design with Nonequivalent Control Group Design. Data analysis was done by inferential statistical test by using the formula Paired Sample Test and Independent Samples Test. The conclusion is the content mastery service is equally effective to enhance the public speaking ability. It can be seen clearly that the probability figure Asmyp. Sig. (2-tailed) public speaking ability in experimental group and control group is 0,000. It showed the probability under alpha of 0.05 (0.000 <0.05).Â Keywords: Content Mastery Service, Public Speaking, StudentSkills.